Dissolved Oxygen Dispersion Model Within Green Mussel Farming Area in Sri Racha Bay, Chonburi Province, Thailand - Anongponyoskun, Monton; Tharapan, Sunthari; Intarachart, Alongot; Doydee, Puvadol; Sojisuporn , Pramot (Agriculture and Natural Resources, 2012)
Dissolved oxygen (DO) is a major parameter in the aquatic environment and it is also necessary for all marine organisms, including mollusks. Thus, a case study was developed to model the DO distribution within a green mussel farming area in Sri Racha Bay, Chonburi province, Thailand. The model indicated that the water was well mixed, based on a mass balancing equation. The DO concentration varied depending on the sources and sinks of the DO which were applied to the model. A solution for the model was considered by an implicit method of successive over relaxation. In the model, the velocity of water was computed by the Princeton Ocean Model (POM). The output of the POM revealed that the seawater moved northward during the flood tide, while during the ebb tide, it moved southward with a maximum speed approximately 1 m.sec-1. The model was applied by adding and removing DO terms which were obtained from empirical experiments. On 29 January 2010 at 2100 hours, when low tide occurred, the DO concentration in the center of a floating raft of green mussel (Perna viridis) was lowest while the advection of water was dramatically slackened. Moreover, during night time, when there was no photosynthesis, the DO concentration was lowest. The results obtained from the model were acceptable compared with actual field observations. Similarly, the pattern of DO dispersion from the prediction at low tide also corresponded to the pattern of DO dispersion from the survey at low tide. Thus, the model could be used as a tool for predicting and estimating the amount of DO in a marine culture area in order to increase production and the preservation of the environment.